Degradation of Azo Dye by Dye-Degrading Bacteria (Stamford Journal of Microbiology, 2024)
Synthetic aromatic compounds consisting of various functional groups are known as dyes. These colored compounds are often discharged in effluents, and they are very dangerous to aquatic life. The study was carried out to study potential azo dye-degrading bacteria. Bacteria were isolated from 9 soil and 7 effluent samples collected from different parts of Kathmandu Valley. Isolated bacteria were tested for dye tolerance and dye-tolerant bacteria were subjected to decolorization of three acid dyes: acid yellow 25, acid green 23 and acid orange 7. A change in optical density was observed to study the impact of inoculum concentration. All 19 isolated potential bacteria were identified by morphological and biochemical tests. Among these, 6 (60%) of Gram-positive and 4 (50%) of Gram-negative bacteria were dye tolerant. Three bacteria SO2-3W, SO3-4W and S16-4P were able to decolorize acid green 23. The impact of the increase in inoculum concentration was increased in decolorization percentage. SO2-3W, SO3-4W and S16-4P were identified as Bacillus spp. and Pseudomonas aeruginosa, respectively. The ability of Bacillus spp. and Pseudomonas spp. to tolerate and decolorize textile dyes at high concentrations encourages their use as a potential bioinoculant in the treatment of textile wastewater.Stam. J. Microbiol. 2024;14(1):1-4